Building Spaces for Dialogues to Rethink Evaluator Competencies: Lessons from the Webinars Organized by the Evaluation Centre for Complex Health Interventions - Sanjeev Sridharan; April Nakaima; Rachael Gibson; Claudeth White; Asela Kalugampitiya; Randika De Mel; Madhuka Liyanagamage; Ian MacDougall (The Evaluation Center at Western Michigan University, 2023)
Background:  There is a need to rethink evaluator competencies given the harsh and paralyzing realities of COVID.  The pandemic was a time where there was a need to balance diverse perspectives given the limited scientific evidence that existed when faced with a genuinely unprecedented time. In the Fall of 2021 (September to October), the Evaluation Centre for Complex Health Interventions in partnership with the Asia Pacific Evaluation Association organized a three-part webinar series in response to the multiple issues that surfaced during COVID-19, and specifically, the implications of the pandemic for rethinking evaluator competencies and evaluator training. The presenters were from multiple countries including India, Canada, USA, UK, and South Africa. Purpose: The presenters pushed for more responsive evaluation approaches to address inequities and sustainability and for a decolonized approach to knowledge building.  The webinar raised a number of themes that have potential implications for future discussions on evaluator competencies including:  enhancing evaluation contributions to the Sustainable Development Goals (SDGs), the need to rethink evaluation criteria,  the need to embrace and address varieties of uncertainties,  focus on diversity and heterogeneity;  understanding the role of contexts in complex programs and policies;  the need to reconceptualize sustainability;  being more explicit about inequities and vulnerabilities; and the need to pay attention to systems and system dynamics. Setting:  The webinars were organized by the Evaluation Centre and the Asia Pacific Evaluation Association on a Zoom platform. Intervention: Not applicable. Research Design: Not applicable. Data Collection and Analysis: Not applicable. Findings: Not applicable.